INVESTMENT EFFECT BASED ON INVESTMENT OBJECTIVES AND EXPERIENCE ON INVESTMENT DECISIONS FROM A BEHAVIORAL FINANCIAL PERSPECTIVE - S. Syahyono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This article aims to examine the effect of objective-based investment and investment experience on investment decisions made by investors to overcome bias or errors in decision making caused by cognitive limitations or other psychological-emotional factors as contained in behavioral finance studies (Behavioral Finance). The method used is descriptive quantitative. The sampling technique used the purposive sampling technique. The results of the study show that objective-based investment has a positive effect on investment decisions, while investment experience has a negative effect. Based on the results of the study, it can be concluded that investment decisions can be improved in line with the increasing realization of goal-based investments. Meanwhile, investment experience needs to go through other factors to increase accuracy in making investment decisions.